Kajian Perbandingan Pengaturan Sanksi Pidana Bagi Pelaku Tindak Pidana Korupsi di Indonesia dan di China - Haryono; Hatarto Pakpahan (MLJ Merdeka Law Journal, 2026)
This research aims to examine the comparison of criminal sanction regulations for perpetrators of corruption crimes in Indonesia and China, as well as to discover the differences in sanction regulations between the two countries. This research is expected to develop academic skills in conducting normative legal research, understanding research methodology, conducting legal material analysis, and academic writing for the author, as well as broadening insights regarding the legal comparison of both countries for the author and society. In practice, the corruption rate in Indonesia is higher than in China, and the magnitude of losses suffered by the state hampers development, which is highly detrimental to the national economy, thus prompting the author to conduct this research. As the result of the research, the author provides suggestions to government institutions authorized to enact laws, specifically the President and the House of Representatives (DPR), to update several articles in the Anti-Corruption Law (namely Articles 2, 3, 5, 6, 7, 8, 9, 10, 11, 12, and 13). The renewal of this law strongly requires new rules regarding the threat of criminal sanctions based on the magnitude of state losses caused by the corruption crime itself, along with other stricter supporting regulations